2002
DOI: 10.1029/2001ja900152
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic negative sudden impulses: Interplanetary causes and polarization distribution

Abstract: [1] We made a study of the characteristics of geomagnetic negative sudden impulses (SI À s) identified in the midlatitude geomagnetic SYM indices and the causative structures in the solar wind using data from the Wind and ACE spacecraft. A total of 28 SI À s with an amplitude larger than 20 nT in the H component SYM index were found over the period 1995 through 1999, with 50% of them occurring in conjunction with a positive sudden impulse, SI + (i.e., SI pair). In the SI pairs the amplitude of SI À was almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 37 publications
1
65
0
1
Order By: Relevance
“…Oscillations of magnetic field lines can be sustained in the magnetospheric plasma. Lower frequency waves contain more wave power and the power levels vary roughly inversely with the wave frequency [56]. A schematic overview of the relationship between various waves and energetic electrons is shown in Figure 4.…”
Section: Ulf Waves Interaction With Energetic Particles In the Magnetmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations of magnetic field lines can be sustained in the magnetospheric plasma. Lower frequency waves contain more wave power and the power levels vary roughly inversely with the wave frequency [56]. A schematic overview of the relationship between various waves and energetic electrons is shown in Figure 4.…”
Section: Ulf Waves Interaction With Energetic Particles In the Magnetmentioning
confidence: 99%
“…the front edge of the Heliosphere Plasma Sheet (HPS) [55]. Takeuchi et al [56] have undertaken a statistical investigation of interplanetary/solar wind sources of the solar wind dynamic negative impulses. They have found that the negative impulses are usually associated with solar wind discontinuity embedded within CIR, as well as the front edge of the interplanetary magnetic clouds and the trailing edge of HPS.…”
Section: Ulf Waves Excited By Both Positive and Negative Solar Wind Dmentioning
confidence: 99%
“…As it provides one minute resolution, this index can be used to investigate the effects of P dyn pulses (e.g. Takeuchi et al, 2002). The quick look values for the upper and lower auroral electrojet indices (AU and AL, respectively) are given in the bottom two panels of Fig.…”
Section: Observations Of the Sscmentioning
confidence: 99%
“…The signature of expansion is a negative sudden impulse (SI − ) in the horizontal component of the geomagnetic field measured at mid to low latitudes (e.g. Takeuchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Positive impulses at the front edge of the Heliosphere Plasma Sheet (HPS) may also act as a source of ULF waves (Winterhalter et al 1994). Statistical analysis of IP shocks and solar wind sources of negative impulses (Takeuchi et al 2002) suggest they are mostly caused by the solar wind discontinuity embedded inside CIRs, the front edge of interplanetary magnetic clouds, and the trailing edge of the HPS. Small-scale plasma bubbles located within CIRs also produce negative and positive pressure impulses at the front and trailing edge of the bubbles, respectively.…”
Section: Introductionmentioning
confidence: 99%